Developing Entrepreneurship Education Model in Improving the Skills of Recycling of Elementary School Students - Desak Made Dharmawati; Nadiroh Nadiroh; Arita Marini (Al Ibtida: Jurnal Pendidikan Guru MI, 2020)
AbstractThis study was about developing an entrepreneurial education model in improving the recycling skills of elementary school students as well as to find out the improvement of aspects of knowledge, aspects of attitudes, and aspects of student skills through the entrepreneurship education model. This development research adopted the development design of Borg & Gall. Model validation is done through expert judgment. Model trials were conducted in class V (five) in three elementary schools. Research data obtained through observation, questionnaires, and interviews. The results of this study indicate that the development of entrepreneurship education models in improving students' recycling crafts skills in primary schools based on the results of expert validation by 66.94% with a high category. The entrepreneurship education model developed can also increase the entrepreneurial knowledge aspect by 76.16%, the attitude aspect by 79.84%, and the entrepreneurial skills aspect by 82.64%. This means that the increase in all three aspects is in the high category. Therefore, this entrepreneurship education model can be an alternative in developing entrepreneurship education in elementary schools.Keywords: entrepreneurship education, recycling crafts, elementary school students.AbstrakPenelitian ini bertujuan untuk mengembangkan model pendidikan kewirausahaan dalam meningkatkan keterampilan kerajinan recycling siswa sekolah dasar sekaligus untuk mengetahui peningkatan aspek pengetahuan, aspek sikap, dan aspek keterampilan siswa melalui model pendidikan kewirausahaan tersebut. Penelitian pengembangan ini mengadopsi desain pengembangan dari Borg & Gall. Validasi model dilakukan melalui expert judgment. Uji coba model dilakukan di kelas V (lima) di tiga Sekolah Dasar. Data hasil penelitian diperoleh melalui observasi, angket, dan wawancara. Hasil penelitian ini menunjukkan bahwa pengembangan model pendidikan kewirausahaan dalam meningkatkan keterampilan kerajinan recycling siswa di sekolah dasar berdasarkan hasil validasi ahli sebesar 66,94 % dengan kategori tinggi. Model pendidikan kewirausahaan yang dikembangkan juga dapat meningkatkan aspek pengetahuan kewirausahaan sebesar 76,16%, aspek sikap sebesar 79,84%, dan aspek keterampilan kewirausahaan sebesar 82,64%. Artinya peningkatan ketiga aspek tersebut dalam kategori tinggi. Oleh karena itu, model pendidikan kewirausahaan ini dapat menjadi alternatif dalam mengembangkan pendidikan kewirausahaan di sekolah dasar.Kata kunci: pendidikan kewirausahaan, kerajinan daur ulang, siswa sekolah dasar.Â